2015
DOI: 10.1111/ijun.12084
|View full text |Cite
|
Sign up to set email alerts
|

Standardized intermittent catheterisation education improves catheterisation compliance in individuals with spinal cord injury

Abstract: Intermittent catheterisation (IC) is considered the gold standard for bladder dysfunction‐related voiding problems following spinal cord injury (SCI). Despite this, up to 50% of individuals were no longer using IC 5 years after discharge from the rehabilitation centre. Hence, we initiated the IC Education Programme to offer standardized IC training and improve adherence. The programme was a European initiative undertaken by eight rehabilitation centres in Norway, France and Italy. The aim of this study is to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…A short-come of the previous studies did not assess quality of educational initiatives, as no objective feedback was obtained from the patients. In a European initiative undertaken by eight rehabilitation centres in Norway, France, and Italy, it was shown that a good education programme can improve adherence to IC during the first year at home (99 vs. 83% for the Education Programme and control groups, respectively; p < 0.05) [98]. From a clinical point of view, comprehensive training on IC technique should be provided to neurourological patients.…”
Section: The Model: User Compliance/adherencementioning
confidence: 99%
“…A short-come of the previous studies did not assess quality of educational initiatives, as no objective feedback was obtained from the patients. In a European initiative undertaken by eight rehabilitation centres in Norway, France, and Italy, it was shown that a good education programme can improve adherence to IC during the first year at home (99 vs. 83% for the Education Programme and control groups, respectively; p < 0.05) [98]. From a clinical point of view, comprehensive training on IC technique should be provided to neurourological patients.…”
Section: The Model: User Compliance/adherencementioning
confidence: 99%
“…Since this was a retrospective study on data collected routinely according to the evidence-based documentation of the continence clinic, no ethical approval was required, similar to other nursing studies published in the international urological literature. 26…”
Section: Ethicsmentioning
confidence: 99%
“…All patients provided informed consent to being interviewed and completing the questionnaire and were informed of the possibility of anonymous data publication. Since this was a retrospective study on data collected routinely according to the evidence‐based documentation of the continence clinic, no ethical approval was required, similar to other nursing studies published in the international urological literature 26 …”
Section: Ethicsmentioning
confidence: 99%